Plan of Indian Reserves, Alexandria, Cariboo District - Surveyor General of British Columbia (1883)
Surveyed by W.S. Jemmett, 1883-1884, and traced by W. Hammond. [Signed by P. O'Reilly, Indian Reserve Commissioner, 4 June 1884.] [Approved by William Smithe, Chief Commissioner of Lands and Works, no date.]